2019
DOI: 10.1016/j.jhsg.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Acute Carpal Tunnel Syndrome Following ORIF of Distal Radius Fractures: A Matched Case–Control Study

Abstract: acute carpal tunnel syndrome carpal tunnel release complications distal radius fracture Purpose: Acute carpal tunnel syndrome (CTS) can develop after distal radius fractures (DRFx), necessitating urgent carpal tunnel release (CTR). This complication has not been specifically investigated after open reduction internal fixation (ORIF) of DRFx (DRFx-ORIF). Identifying risk factors would allow for better definition of the indications for prophylactic CTR at the time of DRFx-ORIF. Methods: We reviewed the records o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…There is a paucity of evidence that defines the epidemiology, presenting signs and symptoms and management of patients presenting with ACTS following a distal radius fracture. Studies have shown that AO Type-C fractures, open fractures, fracture translation and diabetes mellitus are risk factors for developing ACTS [16,17]. However, these studies investigated patients who developed ACTS following open reduction internal fixation (ORIF), which may represent a confounding factor for development of ACTS [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…There is a paucity of evidence that defines the epidemiology, presenting signs and symptoms and management of patients presenting with ACTS following a distal radius fracture. Studies have shown that AO Type-C fractures, open fractures, fracture translation and diabetes mellitus are risk factors for developing ACTS [16,17]. However, these studies investigated patients who developed ACTS following open reduction internal fixation (ORIF), which may represent a confounding factor for development of ACTS [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Baseline characteristics and clinical results between patients with high-and low-energy trauma were compared using Fisher exact test for categorical variables and t test for continuous variables. 3,15 P values of <.05 were considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant variables including age, sex, injury mechanism, injury details (open fracture, concomitant injury, polytrauma), and pre-existing median nerve dysfunction were selected based on previous similar studies. 3,15 Distal radius fractures were classified using the AO/Orthopaedic Trauma Association fracture classification by both authors. 16 To mitigate interobserver variability during analysis, all fractures were subsequently grouped as extra-articular (23.A) or intra-articular (partial articular [23.B] and complete articular [23.C]).…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prophylactic carpal tunnel release (CTR) in patients with DRFs is not recommended. 104,105 Acute CTR should be done in patients with persistent and progressive features of acute CTS. 22,23,106,107 Delayed release of more than 36 hours has been associated with irreversible nerve damage, whereas patients released acutely regained full nerve function.…”
Section: Carpal Tunnel Release During Fracture Fixationmentioning
confidence: 99%